Using Performance-Power Modeling to Improve Energy Efficiency of HPC Applications. - Wu, Xingfu; Taylor, Valerie; Cook, Jeanine; Mucci, Philip J. (Computer (00189162), 2016)
Energy-efficient scientific applications require insight into how high-performance computing system features impact the applications' power and performance. This insight results from the development of performance and power models. When used with an earthquake simulation and an aerospace application, a proposed modeling framework reduces energy consumption by up to 48.65 percent and 30.67 percent, respectively.